2012
DOI: 10.1142/s0219455412500526
|View full text |Cite
|
Sign up to set email alerts
|

Data Fusion-Based Structural Damage Detection Under Varying Temperature Conditions

Abstract: A huge number of data can be obtained continuously from a number of sensors in long-term structural health monitoring (SHM). Different sets of data measured at different times may lead to inconsistent monitoring results. In addition, structural responses vary with the changing environmental conditions, particularly temperature. The variation in structural responses caused by temperature changes may mask the variation caused by structural damages.Integration and interpretation of various types of data are criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…The health monitoring of aging structures and infrastructures [ 1 , 2 , 3 , 4 ] is nowadays becoming more and more important, and can exploit devices and methodologies developed within the field of embedded or inclusive smart technologies [ 5 , 6 , 7 ]. The envisioned structural health monitoring (SHM) systems have to sense in real-time the changing environment, so as to send out early warnings if dangerous situations are approached.…”
Section: Introductionmentioning
confidence: 99%
“…The health monitoring of aging structures and infrastructures [ 1 , 2 , 3 , 4 ] is nowadays becoming more and more important, and can exploit devices and methodologies developed within the field of embedded or inclusive smart technologies [ 5 , 6 , 7 ]. The envisioned structural health monitoring (SHM) systems have to sense in real-time the changing environment, so as to send out early warnings if dangerous situations are approached.…”
Section: Introductionmentioning
confidence: 99%
“…Bao et al (2013) employed this formulation for data fusion-based structural damage detection under varying temperature conditions. Here, the temperature change effects on the modal parameters were considered in the construction of the likelihood function for θ in equation (13).…”
Section: Applications Of Bayesian Inference In System Identification mentioning
confidence: 99%
“…Moser and Moaveni (2011) developed several nonlinear models to represent the relationship between the identified natural frequencies and measured temperatures. Bao et al (2012) revealed the relationship between the natural frequencies and temperature conditions with the extracted DSFs of a two-story portal frame structure in the laboratory. These methods require the measurement of varying environmental conditions, therefore are not easy to apply to the large-scale structures.…”
Section: Introductionmentioning
confidence: 99%